Genetic Improvement of Olives, Enzymatic Extraction and Interesterification of Olive Oil - Contesini, Fabiano Jares; Teixeira, Camilo Barroso; Speranza, Paula; Lopes, Danielle Branta; Carvalho, Patrícia de Oliveira; Sato, Hélia Harumi; Macedo, Gabriela Alves (IntechOpen, 2012)
None